2009
DOI: 10.1073/pnas.0907511106
|View full text |Cite|
|
Sign up to set email alerts
|

Essential role of MALT1 protease activity in activated B cell-like diffuse large B-cell lymphoma

Abstract: A key element for the development of suitable anti-cancer drugs is the identification of cancer-specific enzymatic activities that can be therapeutically targeted. Mucosa-associated lymphoid tissue transformation protein 1 (MALT1) is a proto-oncogene that contributes to tumorigenesis in diffuse large B-cell lymphoma (DLBCL) of the activated B-cell (ABC) subtype, the least curable subtype of DLBCL. Recent data suggest that MALT1 has proteolytic activity, but it is unknown whether this activity is relevant for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
219
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(227 citation statements)
references
References 34 publications
7
219
1
Order By: Relevance
“…4A). Congruent with the previously observed constitutive cleavage of the MALT1 substrates BCL10 and A20 in ABC DLBCL cells (8,9), we found increased constitutive MALT1 activity in all ABC DLBCL cell lines compared with three GCB DLBCL cell lines, despite comparable amounts of MALT1 in the different DLBCL cells (8). Similar to the recombinant GST-MALT1 protease, cellular MALT1 activity was completely blocked by the addition of 50 nM Z-VRPR-FMK to the cleavage reaction (Fig.…”
Section: Pi3k-pdk1 Signaling Controls Viability Of a Subset Of Abc DLmentioning
confidence: 50%
See 2 more Smart Citations
“…4A). Congruent with the previously observed constitutive cleavage of the MALT1 substrates BCL10 and A20 in ABC DLBCL cells (8,9), we found increased constitutive MALT1 activity in all ABC DLBCL cell lines compared with three GCB DLBCL cell lines, despite comparable amounts of MALT1 in the different DLBCL cells (8). Similar to the recombinant GST-MALT1 protease, cellular MALT1 activity was completely blocked by the addition of 50 nM Z-VRPR-FMK to the cleavage reaction (Fig.…”
Section: Pi3k-pdk1 Signaling Controls Viability Of a Subset Of Abc DLmentioning
confidence: 50%
“…The MALT1 protein encodes for a mammalian cystein protease that can cleave BCL10 and A20 and is activated in T cells or ABC DLBCL cells (5-9). MALT1 inhibition is toxic to ABC DLBCL cells (8,9). To examine whether PI3K activity could control constitutive MALT1 activity, we first conducted an assay to measure cellular MALT1 protease activity (Fig.…”
Section: Pi3k-pdk1 Signaling Controls Viability Of a Subset Of Abc DLmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of patient samples performed independently by three groups has revealed that CARMA1 is mutated in about 10% of systemic ABC-DLBCL and 16% of primary central nervous system DLBCL [115][116][117]. The oncogenic mutant of CARMA1 constitutively recruits downstream signaling components [118], and likely induces proteolytic activity of MALT1 [119,120], leading to activation of NF-κB [115].…”
Section: The Role Of Cbm Proteins In Lymphomamentioning
confidence: 99%
“…4d-i, -ii, -iii). Overexpression of API2-MALT1C464A slightly decreased L428 cell proliferation and colony formation, which may be due to the dominant negative effect that inhibits the endogenous activity of MALT1 in B lymphoma cells 20,45 . Interestingly, we observed that L428 cells expressing API2-MALT1 proliferated much faster than the LIMA1a-depleted L428 cells ( Fig.…”
Section: Lima1a Silencing or Cleavage Inhibits Tumour Suppressionmentioning
confidence: 99%